3-(4-Chlorophenyl)-5-phenyl-1,2,4-triazolo[3,4-a]isoquinoline - Khan, F. Nawaz (International Union of Crystallography, 2010)
In the title molecule, C(22)H(14)ClN(3), the triazoloisoquinoline ring system is approximately planar, with an r.m.s. deviation of 0.033 (2) Å and a maximum departure from the mean plane of 0.062 (1) Å for the triazole ring C atom, bonded to the benzene ring. The benzene and phenyl rings are twisted by 57.02 (6) and 62.16 (6)°, respectively, to the mean plane of the triazoloisoquinoline ring system. The molecule is stabilized by a weak intramolecular π–π interaction [centroid–centroid distance = 3.7089 (10) Å] between the benzene and phenyl rings. In the crystal structure, weak intermolecular C—H⋯N hydrogen bonds and C—H⋯π interactions link the molecules.